Symbolic Forms for a New Humanity : Cultural and Racial Reconfigurations of Critical Theory - Cornell, Drucilla (Just ideas., 2010)
In dialogue with Afro-Caribbean philosophy, this book seeks in Cassirer's philosophy of symbolic forms a new vocabulary for approaching central intellectual and political issues of our time.